Desempeño docente y rendimiento académico en matemática de los alumnos de una institución educativa de Ventanilla - Callao - Monrroy Almonte, Margot (2012)
This research is not experimental and correlational descriptive design aims to meet the educational performance and its relationship to academic performance of students in a school of Ventanilla - Callao, with a population sample of 94 students, aged between 11 and 13. A survey and a test of academic achievement in the area of mathematics, proceeding with the collection of data for the interpretation thereof. The results of research on teacher performance determine that there is a trend of regular level; addition, academic performance in mathematics was also prone to regular level. With respect to the relationship we found a positive correlation between student achievement and teacher performance components. We also found significant difference between the average teacher performance by levels of academic performance.